Analysis of the Influence of Israeli Boycott on Fundamental Factors and Economic Growth with Changes in Profits as Intervention Variables in Food and Beverage Franchise Companies Origin of the United States in Indonesia - Yusro, Muhamad Wahyu; Sishadiyati (Indonesian Journal Publisher, 2025)
This study aims to analyze the impact of the boycott of Israel on the fundamental factors and economic growth of food and beverage (F&B) companies from the United States, with changes in profits as an intervening variable. The independent variables analyzed include Net Profit Margin (NPM), Current Ratio (CR), and Total Asset Turnover (TATO), while the dependent variable is the company's economic growth. The method used is a quantitative approach with multiple linear regression and path analysis to test for direct and indirect influences. Data was obtained from the financial statements of multinational companies such as McDonald's, Starbucks, and Domino's Pizza that were affected by the boycott. The results showed that TATO had a negative and significant effect on changes in profit and economic growth directly, as well as an indirect effect on economic growth through changes in profit, which was proven to be significant through the Sobel test (Z = 2.55; p < 0.05). In contrast, NPM and CR did not show a significant influence either directly or indirectly. Thus, the efficiency of asset utilization (TATO) is the most dominant factor in influencing the company's economic growth in situations of socio-political pressure such as boycotts.